Meaning and Modularity: The Multivalence of "Mechanism" in Sociological Explanation. (September 2019) - Knight, Carly R.; Reed, Isaac Ariail
Mechanisms are ubiquitous in sociological explanation. Recent theoretical work has sought to extend mechanistic explanation further still: into cultural and interpretative analysis. Yet it is not clear that the concept of mechanism can coherently unify interpretation and causal explanation within a single explanatory framework. We note that sociological mechanistic explanation is marked by a crucial disjuncture. Specifically, we identify two conflicting mechanistic approaches: Modular mechanism models depict counterfactual dependence among independent causal chains, whereas meaningful mechanism models depict relational interdependence among semiotic assemblages. This disjuncture, we argue, is grounded in incompatible causal foundations and entails mechanistic models with distinct and conflicting evidentiary standards. We conclude by proposing a way forward: a sociological pluralism that is attentive to the productive incongruity of our distinct explanatory models.